2021
DOI: 10.1161/jaha.120.019238
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of Patients With Heart Failure With Reduced Ejection Fraction and Chronic Obstructive Pulmonary Disease: Insights From PARADIGM‐HF

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a common comorbidity in heart failure with reduced ejection fraction, associated with undertreatment and worse outcomes. New treatments for heart failure with reduced ejection fraction may be particularly important in patients with concomitant COPD. Methods and Results We examined outcomes in 8399 patients with heart failure with reduced ejection fraction, according to COPD status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Patients with COPD were less likely to be treated with a beta blocker and had more severe functional limitation and impairment of quality of life than participants without COPD. While each of these findings are similar to those reported in patients with HFrEF with COPD, 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 there were also differences. Higher levels of NT‐proBNP have been reported in patients with HFrEF with COPD, 19 , 21 , 24 , 28 , 29 compared with patients with HFrEF without COPD.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Patients with COPD were less likely to be treated with a beta blocker and had more severe functional limitation and impairment of quality of life than participants without COPD. While each of these findings are similar to those reported in patients with HFrEF with COPD, 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 there were also differences. Higher levels of NT‐proBNP have been reported in patients with HFrEF with COPD, 19 , 21 , 24 , 28 , 29 compared with patients with HFrEF without COPD.…”
Section: Discussionsupporting
confidence: 85%
“…While each of these findings are similar to those reported in patients with HFrEF with COPD, 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 there were also differences. Higher levels of NT‐proBNP have been reported in patients with HFrEF with COPD, 19 , 21 , 24 , 28 , 29 compared with patients with HFrEF without COPD. AF was more frequent in patients with HFrEF with COPD, compared with those without.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, the often-unjustified rejection of BB use is a common attitude in clinical practice. The results obtained in this study were in agreement with others that confirmed the underuse of BBs in patients affected by HF and concomitant COPD compared to patients without COPD ( 10 , 53 , 68 ); these data were also relevant at hospital discharge with an increased gap of up to 15% in disfavor of COPD vs. patients with HF alone ( 69 , 70 ). The limited prescription of BBs in this population is related to the onset of adverse respiratory effects mediated by β2-adrenoceptors blockade in the airways ( 71 , 72 ).…”
Section: Discussionsupporting
confidence: 92%
“…Using a non-standard definition (either self-reported by the patient or based on physician assessment, COPD treatment, or from review of the medical notes) the prevalence ranges between 10 and 25% ( Table 1 ). 20–28 Using spirometry to define the presence of COPD, the prevalence is higher and ranges between 25 and 50% ( Table 2 ). 29–33 The reasons for this discrepancy is unclear, but it may be due to undiagnosed COPD in patients with HF: the patient is breathless and the clinician has objective evidence of cardiac dysfunction (raised natriuretic peptide levels and/or reduced left ventricular ejection fraction (LVEF)), another potential cause of the symptoms may go overlooked.…”
Section: Prevalence Of Copd In Patients With Hfmentioning
confidence: 99%